Chuanicosmetura gen. nov. of the tribe Meconematini (Orthoptera: Tettigoniidae) from southwest China and Chuanicosmetura emarginata (Liu, 2000) comb. nov. - Guo, Qi; Wang, Tao; Shi, Fu-Ming (Zootaxa, 2021)
Chuanicosmetura gen. nov. (Orthoptera: Tettigoniidae: Meconematinae) is established based on Chuanicosmetura emarginata (Liu, 2000) comb. nov. In this paper, this species was redescribed, and the male is firstly reported. Illustrations of important morphological characters are provided.